Penentuan Harga Pokok Penjualan Pada Petani Jagung Di Desa Limang Kecamatan Tigabinanga Kaburapaten Karo - H. Kersna Minan; Listiorini; Iman Indrafana KH; Ade Indah Sari (JPM: Jurnal Pengabdian Masyarakat, 2022)
Most of the corn farmers in Limang Village, Tiga Binanga District, Karo Regency do not really understand and know the basic concept of bookkeeping as a business support for expanding and developing investments in the future. This activity aims to provide basic knowledge about simple bookkeeping concepts for recording standardized transactions according to the bookkeeping version that has been known in the field of trading business and also in banking. The hope of this activity is that the farmers in Limang Village are able to prepare and present a Cost of Goods Sold Report in a simple form so that if their business progresses in the future, after 2 years they can get a micro loan from the bank for expanding and developing their business in the future.